Dementia Literacy among Community-Dwelling Older Adults in Urban China: A Cross-sectional Study - Zhang, Haifeng; Loi, Samantha M.; Zhou, Shu’aijun; Zhao, Mei; Lv, Xiaozhen; Wang, Jing; Wang, Xiao; Lautenschlager, Nicola; Yu, Xin; Wang, Huali (Frontiers in Public Health, 2017)
Objective Delay in seeking diagnosis of dementia is common in China. Misinformation and poor knowledge about dementia may contribute to it. The study was designed to explore the nationwide dementia literacy among older adults in urban China and to investigate the factors associated with overall dementia literacy. Methods In a cross-sectional study, a convenience sample of 3,439 community-dwelling old adults aged 60 and over was recruited from 34 cities in 20 provinces between June 20 and August 20, 2014. All participants were administered the face-to-face mental health literacy questionnaire, which included the prevalence, symptoms, intention, and options for treatment of dementia. Stepwise multivariate regression analysis was used to explore factors associated with overall dementia literacy. Results The response rate was 87.4%. The overall dementia literacy was 55.5% (SD = 20.9%) among all respondents. The correct response rate was higher for questions on symptoms (58.7–89.6%), but lower for questions on the prevalence (22.2%) and choosing appropriate professional care personnel (22.2%). Being male [OR = 1.256, 95% CI (1.022–1.543)], having lower per capita annual income [OR = 1.314, 95% CI (1.064–1.623)], lower education [OR = 1.462, 95% CI (1.162–1.839)], and suspected depression [OR = 1.248, 95% CI (1.009–1.543)] were negatively associated with overall dementia literacy. Conclusion Dementia literacy among community-dwelling older adults in urban China remains very low, in particular about the impact of dementia and appropriate treatment personnel. Community educational programs aiming to close this knowledge gap are encouraged to focus on those in the population at highest risk of low dementia literacy.